Two Friends (Schooner) pass - Two Friends (Schooner)
Pass, bearing signatures of Thomas Jefferson and James Madison, verifying the neutrality of the schooner Two Friends that sailed out of New York, N.Y., under Daniel B. Hussey, captain.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hussey, Daniel B; Jefferson, Thomas, -- 1743-1826.; Madison, James, -- 1751-1836.; Neutrality; Ship's papers -- 19th century; New York (N.Y.) -- Commerce